Essays on local labor markets, ﬁrm taxation and worker mobility - Korfmann, Philipp (Technische Universität Dortmund, 2020)
This thesis investigates the causes and consequences of regional disparities in Germany and consists of three self-contained essays. Each essay utilizes spatially fine-grained microdata for Germany. They differ in focus and methodology but are all inseparably related through the spatial level of analysis. Chapter one provides introductory remarks. The second chapter studies the relative impact of two distinct local business tax instruments on workers' wages. While the primary contribution is the estimation of the effect of a revenue-neutral substitution between two tax instruments, the chapter provides evidence of the amplification of cross-regional wage disparities through local taxation. The third chapter relates regional unemployment differentials to worker flows, recovers underlying structural variations across regions, and investigates the impact of optimal local labor market policies that attenuate within market inefficiencies and balance the adverse effect of unemployment insurance benefits. The fourth chapter studies the characteristics of individual inter-regional migration decisions of employed workers and examines the relationship between individual earnings gains and location characteristics. Chapter five concludes.
Keywords: Local labor markets; Worker mobility; Local business taxation; 330; Regionaler Arbeitsmarkt; Arbeitsmobilität; Unternehmensbesteuerung